Participation and performance trends in the ITU Duathlon World Championship from 2003 to 2017 - Nikolaidis, P. T.; Villiger, E.; Knechtle, B. (The Journal of Strength and Conditioning Research, 2021)
Participation and performance across years have been studied extensively in various endurance and ultra-endurance sports; however, less information exists with regards to duathlon (i.e., Run 1, Bike, and Run 2). The aim of this study was to examine performance and participation trends of duathletes competing either to short (10-km Run 1, 50-km Bike, and 5-km Run 2) or to long distance (10-km Run 1, 150-km Bike, and 30-km Run 2) in the Powerman World Championship "Powerman Zofingen." We analyzed 7,951 finishers (women, n = 1,236, age 36.7 ± 9.1 years; men, n = 6,715, 40.1 ± 10.1 years) competing in "Powerman Zofingen" from 2003 to 2017. Men were faster than women by 8.2% (171 ± 21 minutes vs. 186 ± 21 minutes, p < 0.001, Eta 2 = 0.068) and 7.5% (502 ± 57 minutes vs. 543 ± 64 minutes, p < 0.001, Eta 2 = 0.068) in the short and long distances, respectively. Women were younger than men by 4.6 years (35.0 ± 9.0 years vs. 39.6 ± 10.5 years, p < 0.001, Eta 2 = 0.026) and 1.8 years (38.8 ± 8.7 years vs. 40.6 ± 9.5 years, p < 0.001, Eta 2 = 0.005) in the short and long distances, respectively. An increase of women finishers across years in the long distance was observed (e.g., n = 19 in 2003 and n = 58 in 2017; p < 0.001), whereas no change was shown in short distance and men finishers. The men-to-women ratio (MWR) decreased across years in the long, but not in the short distance. No change of race time across years was observed. The sex difference in race time increased in long distance (p = 0.014), whereas it did not change in the short. Age increased across years in both sexes and distances (p < 0.001). The sex difference in age decreased in the long (p = 0.007), but not in the short distance. In summary, the number of women finishers increased and the MWR decreased in the long distance. The age of the finishers increased across years, and their performance remained unchanged. The increase of the sex difference in race time in the long distance might be attributed to the increased number of women finishers.